Comparative estimation of technical efficiency in livestock-oil palm integration in Johor, Malaysia: evidence from full and partial frontier estimators - Gabdo, Bashir Hamman; Abd Latif, Ismail; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir (Canadian Center of Science and Education, 2014)
Two full frontiers (DEA and FDH) and two partial frontiers (order-alpha and order-m) were employed on the same data set for comparative estimation of technical efficiency in the goat-oil palm and cattle-oil palm integration systems. Data were collected from 255 livestock-oil palm integrated smallholder farms in Johor, Malaysia for the 2011 production season. Although the estimators differ in their assumptions but the technical efficiency estimates from the four distinct estimators based on the data set used appear to be similar both in magnitude and distribution as most farms produce either on the frontier or very close to the frontier. The small nature of the farms accounts for the negligible inefficiency recorded; as recommendation, larger farm size is indeed a policy tool that can guarantee frontier production to all farms.